SISTEM INFORMASI PENENTUAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING PADA CV NILA MAS - Nurhadi Nurhadi; Edi Supratman; Qoriani Widayati (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2020)
Today’s business development is progressing day by day. To maintain competition and develop business in CV Nila Mas, it must follow the existing technological developments. The stages carriedout in the study consisted of communication, planning, modelling, construction and develoyment. The method used for calculating cost of production is the full costing method and the system created using the waterfall method. The information system produced is an information system determining the price of production, which can calculate the cost of production at CV Nila Mas. With the existence of an information system to determine the price of this production, it is hoped that CV Nila Mas can calculate the cost of production at CV Nila Mas